2015
DOI: 10.3389/fpls.2015.00788
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of fruit stored under cold conditions using controlled atmosphere in Prunus persica cv. “Red Pearl”

Abstract: Cold storage (CS) can induce a physiological disorder known as chilling injury (CI) in nectarine fruits. The main symptom is mealiness that is perceived as non-juicy fruit by consumers. Postharvest treatments such as controlled atmosphere (CA; a high CO2 concentration and low O2) have been used under cold conditions to avoid this disorder. With the objective of exploring the mechanisms involved in the CA effect on mealiness prevention, we analyzed transcriptomic changes under six conditions of “Red Pearl” nect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 55 publications
2
32
0
Order By: Relevance
“…A). Fruits with a postharvest‐controlled atmosphere treatment that decreases mealiness (Sanhueza et al ) and from varieties with low susceptibility to mealiness (Almeida et al ) displayed higher expression levels of ACO1 during the ripening that follows cold storage, supporting the relevance of ACO1 in avoiding mealiness.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A). Fruits with a postharvest‐controlled atmosphere treatment that decreases mealiness (Sanhueza et al ) and from varieties with low susceptibility to mealiness (Almeida et al ) displayed higher expression levels of ACO1 during the ripening that follows cold storage, supporting the relevance of ACO1 in avoiding mealiness.…”
Section: Discussionmentioning
confidence: 98%
“…Transcription factors (TFs), agronomic traits‐related QTLs and sensitive/resistant to chilling varieties have been characterized (Bianchi et al , Nuñez‐Lillo et al ), making P. persica an excellent model to understand chilling injury in plants. RNA‐seq technology ability to detect large number of expressed genes have been successfully used to unfold key molecular processes related to chilling injury in P. persica (Sanhueza et al , Wang et al ), tomato (Chen et al , Cruz‐Mendívil et al ), tea (Zheng et al ), tobacco (Hu et al ) and rice (Shen et al ). In this work, we selected four varieties with contrasting mealiness sensitivity, spanning early and late season varieties, and performed a genome‐wide RNA‐seq analysis to uncover the main mechanisms related to chilling injury in P. persica .…”
Section: Introductionmentioning
confidence: 99%
“…Kaji et al . () found that CO 2 accumulation in packaging causes severe softening of shiitake mushrooms, as it does for peaches, apricots, bananas and other fruits, during storage (Ahmad & Thompson, ; Rebeaud et al ., ; Sanhueza et al ., ). Therefore, it is likely that the relatively low CO 2 content in the packaging of ultrasonic‐treated mushrooms also slowed the softening.…”
Section: Discussionmentioning
confidence: 99%
“…As the moisture content of Figure 5 Changes in the activities of enzymes related to cell wall degradation (a, glucanase; b, chitinase; c, cellulase). Many studies have reported that high concentrations of CO 2 contribute to the softening of fruits, such as peach (Sanhueza et al, 2015), apricots (Rebeaud et al, 2015) and bananas (Ahmad & Thompson, 2015), mainly through decreased starch and the dissolution of pectin. the mushrooms in both the treatment and control groups showed no significant changes (data not shown), we hypothesised that the main cause of mushroom softening was destruction of cell wall induced by depletion of O 2 and accumulation of CO 2 .…”
Section: Discussionmentioning
confidence: 99%